Impact of Cysteine as a Semen Additive on Mitigating the Decline in Sperm Quality due to Summer Stress in Riverine Buffaloes (Bubalus bubalis) - Arunpandian, J; Srivastava, Neeraj; Singh, Gyanendra; Kumar, Brijesh; Jackson, Amala; Chandra, Pradeep; Ghosh, Subrato Kumar; Singh, Sanjay Kumar; Khan , Meiraj Haider (The Indian Journal of Animal Reproduction, 2023)
The seasonal variations such as temperature, rain and humid environment greatly influences reproduction, and semen quality particularly in buffalo bulls, either positively or negatively. The heat stress coupled with freezing and thawing processes generates reactive oxygen species (ROS), which further reduce post-thaw spermatozoa quality. Application of cysteine as a semen additive have been reported to alleviate such damaging effect in canine, buck, bull, human, boar, and rooster. Therefore, objective of this study was to investigate ameliorating effect of cysteine on summer stress on buffalo spermatozoa. For the experiment, 24 ejaculates with individual progressive motility >70, volume >1mL and sperm concentration 1000 million/mL from four Murrah buffalo bulls were collected and divided into four groups as Control (Group-I), and Group-II, III, and IV (4, 8, and 12 mmol cysteine, respectively) containing 80 million spermatozoa per mL. Semen was filled (French mini straw), sealed and equilibrated at 40⸰C and frozen into LN2. The group containing L-cysteine at 4 mmol concentration had higher significant (p<0.05) difference in post thaw motility, viability, plasma membrane integrity and acrosome integrity, TAC, DNA integrity and lower significant (p<0.05) difference in spermatozoa abnormality, LPO and intracellular ROS. Moreover, cysteine concentration at 8 mmol has no beneficial effect compared to the Control, whereas Group-IV had greater adverse effect. This may be due to its toxicity at this concentration. It is evident from the study that the cysteine molecules at 4 mmol concentration produced more pronounced improvement in the freezability potential of buffalo bull spermatozoa.